A scoping review of sport coach education programs: An international perspective. - Shaikh, Majidullah; Santos, Yura Yuka Sato dos; Rodrigue, François; Ciampolini, Vitor; Galatti, Larissa R; Seguin, Cassandra; Brasil, Vinicius Z; He, Chao; Culver, Diane M; Nash, Christine; Milistetd, Michel; Fournier, Karine (Université d'Ottawa | University of Ottawa, 2019)
There has been a lack of synthesis on the existence, effectiveness, and nature of sport coach education programs (CEPs) from a global perspective. As well, given the growth of CEP-related research in the past decade there is a need to amalgamate the results of these studies in order to identify key areas of importance and future directions to inform the improvement of current CEPs. The purpose of this project set out by the International Coach Development Research Team was to generate a greater understanding of sport CEPs that exist around the world, by reviewing literature from 2010-2019 found in English, French, Spanish, and Portuguese language journals. A scoping review methodology was carried out, which is a robust and systematic approach to reviewing literature to generate a broad understanding or descriptions of their contents. Criteria for inclusion included any literature that provided descriptions and/or evaluations of sport CEPs. Exclusion criteria included any non-specific program descriptions or evaluations, papers situated outside of sport coaching domain, papers related to the NCCP and the funding body for this project, any conference abstracts or theses/book chapters, and any papers in languages other than those of focus in this project. Phase I of this review involved collaborating with the University of Ottawa’s librarian to develop a search strategy (Appendix A) and collect literature from eight relevant databases. At the end of Phase I, 3403 records were identified to move forward to the next phase. These records were amalgamated onto a shared review database known as Covidence. Phase II of this review involved screening each title and abstract of these records. Here, each record would require two collaborators to make a decision on it – using the inclusion/exclusion criteria – and any conflicts that arose were resolved by a third collaborator. At the end of Phase II, 398 records were identified to move on to the next phase. Phase III of this review involved collecting full-text copies of each record and screening them. Screening involved two collaborators making decisions on each record, using the inclusion/exclusion criteria, and any conflicts that arose were resolved between the two collaborators. At the end of Phase III, 109 records were selected for the next phase. The bibliography of these records are in Appendix B. Phase IV of this review involved extracting relevant data from the full-text copies of each record into a consolidated spreadsheet. Data included: Authors and year, title, purpose, country, participants and contexts, delivery model, type of research, methodologies, results, and other general findings. These data are displayed in Appendix C. Phase V was a supplementary phase conducted to identify, select, and extract data from any policy and program descriptions that may help to conceptualize the CEP-papers generated from Phases I-IV. Phase VI involved the synthesis of key issues from across the records to help generate a greater understanding of the nature and existence of CEPs across the globe. Three analyses here were performed: (a) content analysis on studies with evaluations, (b) qualitative description of CEP evaluation results, and (c) qualitative descriptions of policy literature and CEP program descriptions. The results of the content analysis consisted of a mix of frequency and descriptive statistics, and were divided into three sections: (a) context and participants, (b) program design, and (c) methodology and methods. The results of the description of CEP results consisted of three themes related to the types of evaluation research, and their sub-themes: (a) outcome: changes in knowledge and skills, behaviour change, attitudes, confidence, and intentions, and athlete outcomes), (b) process: facilitators to learning, challenges to learning, and mediums of training, and (c) implementation: facilitators to delivery, challenges to delivery, and suggestions for program improvement. The results of the program descriptions and policy literature consisted of four themes: (a) descriptions of national and regional sport federations/associations CEPs, (b) policy accreditation of international sport federations, (c) policy accreditation of national governing bodies, sport federations, and Olympic committees, and (d) policy accreditation of Portuguese and Spanish-speaking countries.